2013
DOI: 10.1530/endoabs.32.p519
|View full text |Cite
|
Sign up to set email alerts
|

mTOR, AKT, p70S6K and ERK1/2 levels predict sensitivity to mTOR and PI3K/mTOR inhibitors in human bronchial carcinoids

Abstract: Background: Bronchial carcinoids (BCs) are rare neuroendocrine tumors that are still orphan of medical treatment. Human BC primary cultures may display resistance to everolimus, an inhibitor of the mammalian target of rapamycin (mTOR), in terms of cell viability reduction.\ud \ud Aim: To assess whether the novel dual PI3K/mTOR inhibitor, NVP-BEZ235, may be effective in everolimus-resistant human BC tissues and cell lines. In addition, we search for possible markers of mTOR inhibitors efficacy, that may help in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In randomized controlled trials, everolimus obtained a 65% decrease in the risk for tumor progression in pNETs [7] and a 23% decrease in patients with nonpancreatic NETs (non-pNETs) [9]. In addition, promising preclinical findings suggested that everolimus might be effective in aggressive endocrine neoplasms [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In randomized controlled trials, everolimus obtained a 65% decrease in the risk for tumor progression in pNETs [7] and a 23% decrease in patients with nonpancreatic NETs (non-pNETs) [9]. In addition, promising preclinical findings suggested that everolimus might be effective in aggressive endocrine neoplasms [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of some of the above molecules (in particular p-mTOR and GLUT-1, as well as of the aminoacid transporter LAT-1, were strongly associated with SSTR2A expression, suggesting that somatostatin receptor inhibitor effects may result from mTOR pathway control, and that synergies can be obtained by combined treatments, as suggested in intestinal NETs [47]. Indeed, in in vitro models, bronchial carcinoid cells of patients responding to mTOR inhibitors were shown to have higher levels of phosphorylated mTOR [48].…”
Section: Prognostic and Predictive Molecular Markersmentioning
confidence: 97%
“…Potential markers predicting sensitivity to mTOR inhibitors have been also suggested, such as total mTOR level, AKT, p70S6K (RPS6KB2), and mitogen-activated protein/extracellular signal-regulated kinases (MAPK/ERK) levels in patients with pulmonary carcinoids (20). In SCLC cells, high expression of eukaryotic translation initiation factor 4E (elF4E) was associated with increased resistance to everolimus treatment.…”
Section: Abstract Primary Lung Neuroendocrine Tumors (Nets) Consist mentioning
confidence: 99%